The complete chloroplast genome of eriochloa villosa (thunb.) kunth - Haijun Cheng; Yujie Huang; Mei Li; Longjiang Fan; Jian Li (Mitochondrial DNA. Part B. Resources)
Eriochloa villosa (Thunb.) Kunth, 1829 (Woolly cupgrass), an invasive annual weed in the Poaceae family, poses a significant threat to corn and soybean crop production, resulting in substantial yield reduction. Despite its agronomic importance, genomic resources for this species remain limited. In this study, we report the first complete chloroplast genome assembly of a hexaploid E. villosa, which spans 139,777 base pairs and contains 127 annotated genes. This comprehensive chloroplast genomic characterization provides essential foundational resources for further genetic and evolutionary studies within the Eriochloa genus.